#### Problem Statement: ME Board October 1996

Solve the simultaneous equations:

x + y = – 4

x + z – 1 = 0

y + z + 1 = 0

- A. x = -1, y = -5, z = 3
- B. x = 1, y = 2, z = -3
- C. x = -1, y = -3, z = 2
- D. x = -2, y = -3, z = -1

#### Problem Answer:

The value of **x is equal to -1, y is equal to -3 and z is equal to 2**.

Solution:

### Latest Problem Solving in Fundamentals in Algebra

div.feedburnerFeedBlock ul li {background: #E2F0FD;

list-style-type: none;

margin:0 0 5px 0px;

padding:5px 5px 5px 10px !important;

border: 1px solid #0080ff;

border-radius:8px;

-moz-border-radius:8px;

-webkit-border-radius:8px;

}

div.feedburnerFeedBlock ul li:hover {

background:#ffffff;

}

div.feedburnerFeedBlock ul li a{

color:#ffffff;

text-decoration:none;

}

div.feedburnerFeedBlock ul li a:hover {

text-decoration: underline;

color: #000000;

}

div #creditfooter{

display: none;

}

More Questions in: Fundamentals in Algebra

#### Online Questions and Answers in Fundamentals in Algebra Series

If you liked this, then please subscribe to our YouTube Channel for engineering video tutorials. You can also find us on Twitter and Facebook.